Pre-diabetes: Diagnostic Criteria And Therapeutic Approach (Journal of Chittagong Medical College Teachers' Association, 2019)
Pre-diabetes is defined as Impaired Fasting Glucose (IFG) or Impaired Glucose Tolerance (IGT) after a standard OGTT test. It is a high risk state not only because it may lead to diabetes, but also because of the associated complications such as vascular complications, nephropathy, and neuropathy that have been reported in people with Pre-diabetes. Pathophysiology of pre-diabetes state is linked to two main factors, insulin resistance and the relative deficiency of beta cells, these two mechanisms will eventually lead to abnormal glucose level. Pre-diabetes increases the risk of both microvascular and macrovascular complications. It is also an independent risk for stroke and cardiovascular disease. Early detection of pre-diabetes by screening can help in preventing vascular complications, and helps in changing the natural history of this disease by improving the islet cell function. Lifestyle modification like weight reduction and exercise reduces the risk of T2DM whereas pharmacological treatment with Metformin, Acarbose, Voglibose and Orlistat have all demonstrated significant reductions in progression to T2DM with very few adverse effects. In this review, we shall discuss and highlight the evidences that support the benefits of early intervention in Pre-diabetes and determine the cost effectiveness of lifestyle modification and drug treatment.JCMCTA 2018 ; 29 (2) : 68-75